(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this work is to examine the correlation between the in vitro solubilization process of lipophilic drug fenofibrate prepared as self-emulsifying drug delivery systems, and the in vivo absorption data. In vitro lipolysis model was performed, and the concentration of drug in blood was measured in rats. The in vitro lipolysis model shows low concentration of drug in the aqueous phase, while the in vivo study demonstrates complete drug absorption orally. Poor in vitro in vivo correlation attributed to significant drug transport through lymphatic rout.